The role of accounting idea to reduce the international financial crisis on the financial establishment - Mohamed, Mahdi Abdalla; Mohamed, Musa Abdulla (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to know the role of accounting ideas in mitigating the severity of the financial crises on financial institutions, by formulating a number of assumptions. The most important of these is the relationship between the application of professional standards and accounting policies and limiting the effects of the financial crises and achieving the safety of financial institutions. The study adopted the historical, descriptive approach to arrive at the results of the study depending on the primary sources. The study presented the introduction and four sections, the first, entitled the concept, types and characteristics of financial crises. The second topic is the effects and repercussions of financial crises on financial institutions. The third topic is the role of accounting ideas and professional institutions in financial crises. The fourth topic implications and solution of global financial crises on Sudan. One of the most important results is the absence of financial and economic policies from specialized agencies in Sudan. The study concluded by depending on accounting theorists to protect financial institutions from financial crises. One of the most important recommendation is the need for county to improve its economic relations with foreign countries.